Influence of sawdust particles reinforcement on physical and mechanical properties of High-Density Polyethylene (HDPE) matrix composites - Kuforiji, Catherine; Durowaye, Stephen; Odunitan, Oluwajuwon; Kassim, Kehinde; Lawal, Ganiyu (Kathmandu University Journal of Science Engineering and Technology, 2023)
The influence of sawdust particles reinforcement on the physical and mechanical characteristics of high-density polyethylene (HDPE) matrix composites was studied for application as sustainable wood plastic composites (WPCs) for housing. The WPCs developed by compression moulding method were characterised. The results revealed web-like structures/cross-linking in the microstructure of the samples, which is a characteristic of polymers. The microstructure revealed a good dispersion of sawdust particles and compatibilizer in the HDPE matrix and bonding, which enhanced the properties of the composites. The control sample C exhibited water absorption of 0.22 % whereas sample S8 having 1.1 to 1.4 mm sawdust particles, 30 wt. % of sawdust particles content, and 3 wt. % of compatibilizer exhibited the least water absorption of 0.14 %. The unreinforced HDPE control sample exhibited a tensile strength of 12.53 MPa while sample S7 with the smallest size (less than 1 mm) and 30 wt. % of sawdust particles content, and 7 wt. % of compatibilizer exhibited the highest tensile strength of 16.22 MPa. This is 29.5 % higher than that of the control sample. The control sample exhibited a flexural strength of 10.2 MPa while sample S7 exhibited the highest flexural strength of 14.85 MPa, which is 45.6 % higher than that of the control sample. The control sample exhibited a hardness value of 13.93 HV while sample S7 exhibited the highest hardness value of 19.17 HV, which is 37.6 % greater than that of the control sample. Samples S5, S7, S8, and S9, which contained high content of sawdust particles demonstrated impact energy values of 34.27, 33.14, 35.17, and 36.46 J respectively. The unreinforced control sample demonstrated a low wear rate value of 0.35 g/Nm. However, sample 7 demonstrated the least wear rate of 0.23 g/Nm, which is 34.3 % lower than that of the control sample. In view of these characteristics, the composites especially sample 7, has the potentials for application as a sustainable building material.